2018
DOI: 10.1002/etc.4055
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of the fish embryo acute toxicity (FET) test (OECD 236) in the regulatory context of Registration, Evaluation, Authorisation, and Restriction of Chemicals (REACH)

Abstract: In 2013 the Organisation for Economic Co-operation and Development (OECD) test guideline (236) for fish embryo acute toxicity (FET) was adopted. It determines the acute toxicity of chemicals to embryonic fish. Previous studies show a good correlation of FET with the standard acute fish toxicity (AFT) test; however, the potential of the FET test to predict AFT, which is required by the Registration, Evaluation, Authorisation, and Restriction of Chemicals (REACH) regulation (EC 1907(EC /2006) and the Classifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
88
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 108 publications
(88 citation statements)
references
References 44 publications
(66 reference statements)
0
88
0
Order By: Relevance
“…After significant international validation efforts (Busquet et al 2014), an extension of the test from 48 to 96 h in duration, and omission of the term “replacement to fish acute toxicity” in the introduction of the test guideline (TG), the FET test was finally accepted as an OECD test guideline nearly 8 y later (OECD 2013). However, its universal acceptance as a replacement to the acute fish toxicity test (OECD 1992) has remained an issue because regulators, such as the European Chemicals Agency (ECHA), have not accepted it as a complete replacement (Sobanska et al 2018). A conservative approach to the acceptance of the FET test has been argued due to the existence of some limitations (e.g., neurotoxic mode of action [MoA]) and/or remaining uncertainties (e.g., deviation of some narcotic substances) regarding the FET test (Sobanska et al 2018).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…After significant international validation efforts (Busquet et al 2014), an extension of the test from 48 to 96 h in duration, and omission of the term “replacement to fish acute toxicity” in the introduction of the test guideline (TG), the FET test was finally accepted as an OECD test guideline nearly 8 y later (OECD 2013). However, its universal acceptance as a replacement to the acute fish toxicity test (OECD 1992) has remained an issue because regulators, such as the European Chemicals Agency (ECHA), have not accepted it as a complete replacement (Sobanska et al 2018). A conservative approach to the acceptance of the FET test has been argued due to the existence of some limitations (e.g., neurotoxic mode of action [MoA]) and/or remaining uncertainties (e.g., deviation of some narcotic substances) regarding the FET test (Sobanska et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…However, its universal acceptance as a replacement to the acute fish toxicity test (OECD 1992) has remained an issue because regulators, such as the European Chemicals Agency (ECHA), have not accepted it as a complete replacement (Sobanska et al 2018). A conservative approach to the acceptance of the FET test has been argued due to the existence of some limitations (e.g., neurotoxic mode of action [MoA]) and/or remaining uncertainties (e.g., deviation of some narcotic substances) regarding the FET test (Sobanska et al 2018). Furthermore, it was concluded that “the FET test alone is currently not sufficient to meet the essential information on AFT as required by the REACH regulation” (Sobanska et al 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reviews and comments on the specific case of TiO 2 are published by the parties involved in the process, namely, the authorities (ANSES 2016;ECHA 2017a) and industry (CEPE 2017;TDMA 2018). The other previous research on REACH and CLP focuses largely on various test methods and their applicability in a regulatory context (e.g., Cappelli et al 2015;Alépée et al 2017;Sobanska et al 2017) and in the specific impacts of REACH and CLP on products and applications that are not directly within the scope of these regulations, such as wastes and recycling (Bodar et al 2018), as well as food materials (Geueke and Muncke 2017). Moreover, references to bending regulatory situation for substance groups regarding their assessment according to REACH, for example, nanomaterials and plastics, are discussed (Walser and Studer 2014;Raucher et al 2016;Steensgaard et al 2017;Drobne 2018).…”
Section: Previous Studies Related To Tio 2 Classificationmentioning
confidence: 99%
“…Previous studies show a good correlation of FET with the standard acute fish toxicity (AFT) test (Belanger et al, 2013; Rawlings et al, 2019). Nevertheless, it has been found that the fish embryo toxicity test alone is currently not sufficient to replace the acute fish toxicity data as required by the European REACH regulation (Regulation, Evaluation, Authorisation and Restriction of Chemicals) (Sobanska et al, 2018). However, the authors have suggested that “the test may be used within weight-of-evidence approaches together with other independent, relevant, and reliable sources of information”.…”
Section: Introductionmentioning
confidence: 99%